Environmental taphonomic processes and their effects on skeletal trauma analysis - Vachirawongsakorn, Vijarn (Cranfield University, 2019)
In recent years there has been extensive research focusing on skeletal trauma as a result of different types of weapons inflicted on bone. However, an important factor that has not been investigated in depth is the potential modification to the observed dimensions and morphology of trauma marks after environmental exposure. Detailed information derived from traumatic lesions to bone is highly valuable in forensic anthropological casework. It is important to understand how taphonomic variables, namely the outdoor environment or fire, may alter trauma morphology. Therefore, the aim of this study is to evaluate the influence of different environmental taphonomic agents on fresh and burned bone trauma that have been inflicted by either blunt or sharp instruments. This research used blunt and sharp weapons to inflict trauma on manually macerated porcine ribs (n=364) and femurs (n=60). Subsequently each specimen was examined, analysed, and photographed. Qualitative and quantitative analyses were undertaken using macroscopic, microscopic and radiological techniques to investigate specific traumatic lesions, such as cut and chop marks, as well as bluntinflicted fractures. The traumatised bones were subsequently deposited on the surface or in a buried environment for a pre-determined length of time (6, 12 and 18 months). In addition, sharp force trauma was inflicted on ribs which were then burned at 850°C in a furnace prior to being buried or placed on the surface for 1 month. The samples were then re-examined and the trauma evidence was compared between pre- and post-environmental exposure. The results showed several trends. Surface colour and taphonomic alterations were linked to macro- and micro-environmental factors, and were also dependent on the duration of environmental exposure. Surface-deposited samples underwent higher degrees of degradation than buried samples. In addition, perimortem blunt and sharp force traumatic lesions on the ribs and femurs were still clearly identifiable after 18-month environmental exposure. This study also illustrated that taphonomic modifications of blunt and sharp injuries were different depending on the interaction between bone, the type of trauma and the surrounding environment. Fractures from different types of weapon showed dissimilar responses to environmental variables. ii Pre-exposure bone and different types of depositional environment had an effect on the rate and pattern of taphonomic modifications on dimensions and morphology of the traumatic lesion. The results of this study should enable an improved determination of skeletal trauma analysis after environmental exposure. Moreover, this study has emphasised the need for a combination of macroscopic, microscopic and radiological techniques to analyse taphonomic phenomena. As environmental factors have the potential to conceal perimortem skeletal trauma, this study advises that when carefully examining traumatic lesions on ribs and femurs as an alteration of their dimensions and morphology is likely to have occurred after prolonged environmental exposure.